COMPARATIVE STUDY ON THE ANALGESIC POTENTIAL OF CENTRAL ASIAN SNAKE VENOMS (Western European Journal of Medicine and Medical Science, 2025)
Pain is considered a protective reaction of the body to the dangerous effects of the internal and external environment, and there are various means to eliminate it, and they can have both positive and negative effects. The latter can be cited as an example of addiction. The creation of a new generation of drugs with minimal impact of such negative effects is undoubtedly an urgent task. To solve this problem, the venoms of cobra, gyurza, and rattlesnakes which are common in Central Asia, were studied based on analgesia experiments caused by the «hot plate» and «acetic roots» tests. The obtained results showed that all studied poisons have different levels of analgesic effect. In doing so, cobra venom showed high activity in both pain tests